The Effectiveness of Acceptance and Commitment Therapy on Rejection Sensitivity and Self-Acceptance in Individuals with Visual Impairment - Oveysi, Soleyman; Karimi, Qumarth; Moradi, Omid (Psychological Research in Individuals with Exceptional Needs, 2026)
The present study aimed to examine the effectiveness of Acceptance and Commitment Therapy (ACT) on rejection sensitivity and self-acceptance among individuals with visual impairment. The research employed a quasi-experimental design with a pretest–posttest–follow-up structure including a control group. The statistical population consisted of all visually impaired individuals who were members of associations supporting persons with visual impairment and the Welfare Organization of Kurdistan Province during Spring 2025. From this population, 45 participants were selected using convenience sampling and were randomly assigned to two experimental groups and one control group. Participants completed the Rejection Sensitivity Questionnaire developed by Downey and Feldman (1996) and the Unconditional Self-Acceptance Questionnaire designed by Chamberlain and Haaga (2001) at pretest, posttest, and follow-up stages. Group sessions of Acceptance and Commitment Therapy were conducted for the intervention group based on the treatment protocol proposed by Hayes and Strosahl (2005) across eight 90-minute sessions. Acceptance and Commitment Therapy significantly reduced rejection sensitivity in the intervention group compared with the control group (p = .018). Furthermore, Acceptance and Commitment Therapy significantly increased self-acceptance in the intervention group compared with the control group (p = .005). The findings indicate that Acceptance and Commitment Therapy can be utilized as an effective intervention for reducing rejection sensitivity and enhancing self-acceptance among individuals with visual impairment. The implementation of this therapeutic approach in rehabilitation centers and psychological service settings may play an important role in promoting mental health, emotional adjustment, and improving the quality of life of visually impaired individuals.